2021
DOI: 10.1101/2021.06.16.448661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular census of midbrain dopaminergic neurons in Parkinson’s disease

Abstract: Midbrain dopamine (DA) neurons in the substantia nigra pars compacta (SNpc) project widely throughout the central nervous system, playing critical roles in voluntary movements, reward processing, and working memory. Many of these neurons are highly sensitive to neurodegeneration in Parkinson's Disease (PD), and their loss correlates strongly with the pathognomonic symptoms. To characterize these populations molecularly, we developed a protocol to enrich and transcriptionally profile DA neuron nuclei from postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Here, we show the presence of a ventrally located SOX6 + ,ALDH1A1 + population in human control brains, and that these neurons are selectively diminished in post-mortem PD brains; in contrast, CB + cells were resilient. Our findings are consistent with previous reports using ALDH1A1 and CALB1 as markers ( Liu et al, 2014 ; Yamada et al, 1990 ), as well as recent studies depicting ventral enrichment of SOX6 + neurons in the human SNc ( Kamath et al, 2021 ; Monzón-Sandoval et al, 2020 ). In mice, we found that Sox6 + neurons displayed large transcriptomic differences from Sox6 − neurons that are likely to underpin their different properties ( Figure 7A ).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we show the presence of a ventrally located SOX6 + ,ALDH1A1 + population in human control brains, and that these neurons are selectively diminished in post-mortem PD brains; in contrast, CB + cells were resilient. Our findings are consistent with previous reports using ALDH1A1 and CALB1 as markers ( Liu et al, 2014 ; Yamada et al, 1990 ), as well as recent studies depicting ventral enrichment of SOX6 + neurons in the human SNc ( Kamath et al, 2021 ; Monzón-Sandoval et al, 2020 ). In mice, we found that Sox6 + neurons displayed large transcriptomic differences from Sox6 − neurons that are likely to underpin their different properties ( Figure 7A ).…”
Section: Discussionsupporting
confidence: 93%
“…While there is some utility in performing wholesale single-nucleus transcriptomics on large brain/spinal cord regions in the context of the disease to find the cell type that is responsible for a phenotype, there is a growing appreciation for the necessity to enrich for cell types of interest prior to barcoding and sequencing the RNA from individual nuclei. This approach enables a far more detailed characterization of cell populations of interest, which might otherwise be diluted out by unfavorable stoichiometries [10,11,94].…”
Section: Single-cell Transcriptomics Can Be Applied To Diverse Diseas...mentioning
confidence: 99%
“…An interesting illustration of this phenomenon is the study of Parkinson's disease using single-cell transcriptomics. Recent advances have enabled the cell-type-specific enrichment of nuclei from the dopaminergic midbrain, a development that has provided an unprecedented look at the diversity that may underlie their differential susceptibility in Parkinson's disease [94]. However, aside from motor dysfunction, the most debilitating symptoms associated with Parkinson's disease involve the autonomic nervous system.…”
Section: Single-cell Transcriptomics Can Be Applied To Diverse Diseas...mentioning
confidence: 99%
“…To further investigate LOY in microglia we focused on seven datasets containing subjects with elevated LOY (>10% LOY) [34][35][36][37][38][39][40] (Supplementary Table 3). Microglia were isolated, reclustered and annotated for microglia subtypes (Supplementary Fig.…”
Section: Loy Is Observed Across All Microglia Subtypesmentioning
confidence: 99%
“…These cell-types are often underrepresented in CNS single-cell RNAseq datasets 41 . Kamath 40 , Morabito 39 and Pineda 38 consisted of unsorted nuclei from the substantia nigra, DLPFC and primary motor cortex, respectively.…”
Section: Loy Is Observed Across All Microglia Subtypesmentioning
confidence: 99%